Penegakan Hukum di Wilayah Zona Ekonomi Ekslusif Indonesia terhadap Tindakan Illegal Fishing: Law Enforcement in Indonesia's Exclusive Economic Zone Against Illegal Fishing - Qowim, Muhammad Izzudinil; Sudja’i, Sudja’i; Saktiawan, Pratolo (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Given the large potential of fish resources available in the country's waters, there is interest and desire from various parties to develop and participate in ways that are not in accordance with the code of ethics. The practice of fishing without accountability for the interests of certain individuals or groups can be contrary to government regulations, especially those set by the Indonesian Government. This study aims to determine the categories of actions that are included in the crime of Illegal Fishing and law enforcement against illegal fishing as reviewed from the perspective of criminal law. The research method uses a normative legal method, which applies normative case mapping involving the results of legal actions, as well as an analysis of government regulations that apply a qualitative approach. The results of the study revealed that law enforcement against illegal fishing practices in the Exclusive Economic Zone (EEZ) will be carried out in accordance with the principles of international law as stipulated in Article 73(1) of the 1982 United Nations Convention on the Law of the Sea (UNCLOS) which was later ratified by Law of the Republic of Indonesia Number 17 of 1985 concerning Ratification of the United Nations Agreement on the Law of the Sea United Nations Convention On The Law Of The Sea (UNCLOS). This article emphasizes the authority of the coastal state to investigate, arrest, and prosecute foreign vessels that commit violations in the EEZ.